An Electroactive, Tunable, and Frequency Selective Surface Utilizing Highly Stretchable Dielectric Elastomer Actuators Based on Functionally Antagonistic Aperture Control. Issue 14 (10th February 2016) - Choi, Jun‐Ho; Ahn, Jaeho; Kim, Jin‐Bong; Kim, Young‐Cheol; Lee, Jung‐Yong; Oh, Il‐Kwon
Abstract : An active, frequency selective surface utilizing a silver‐nanowire‐coated dielectric elastomer with a butterfly‐shaped aperture pattern is realized by properly exploiting the electroactive control of two antagonistic functions (stretching vs compression) on a patterned dielectric elastomer actuator.